Composition of Rhizosphere Microbial Communities Associated With Healthy and Verticillium Wilt Diseased Cotton Plants - Wei, Feng; Feng, Hongjie; Zhang, Dezheng; Feng, Zili; Zhao, Lihong; Zhang, Yalin; Deakin, Greg; Peng, Jun; Zhu, Heqin; Xu, Xiangming (Frontiers in Microbiology, 2021)
Rhizosphere microbial communities are known to be related to plant health; using such an association for crop management requires a better understanding of this relationship. We investigated rhizosphere microbiomes associated with two cotton plant cultivars with Verticillium wilt symptoms. Microbial communities were profiled by the amplicon-sequencing, in addition to qPCR quantification of total bacterial and fungal DNA based on the respective 16S and ITS primers. Although the V. dahliae inoculum level was higher in the rhizosphere of diseased plants than in the healthy plants, such a difference only explained a small proportion of variation between diseased and healthy plants. Compared to healthy plants, the diseased plants had much higher total fungal/bacterial biomass ratio. The variability in the fungal/bacterial biomass ratio was much smaller than variability in either fungal or bacterial total biomass among samples within diseased or healthy plants. The diseased plants generally had lower bacterial alpha diversity but such differences in the fungal alpha diversity depended on cultivars. There were consistent differences in both fungal and bacterial communities between diseased and healthy plants. Many rhizosphere microbial groups differed in their abundance between healthy and diseased plants. There was a decrease in arbuscular mycorrhizal fungi and an increase in several plant pathogen and saprophyte guilds in diseased plants based on amplicon-sequencing results. These findings suggested that V. dahliae infection of roots led to rapid changes in rhizosphere microbial communities, with large increases in saprophytic fungi and reduction in the bacterial community.